COVID-19 Vaccination Attitudes and Intention: Message Framing and the Moderating Role of Perceived Vaccine Benefits. Issue 8 (3rd August 2021) - Borah, Porismita; Hwang, Juwon; Hsu, Ying Chia (Louise)
Abstract : The United States is one of the hardest-hit countries by the COVID-19 pandemic and yet there is widespread hesitancy to take the vaccine. In order to address vaccine hesitancy and foster public understanding of the COVID-19 vaccine, it is necessary to strategize public health messages based on evidence. To this end, we use experimental data to examine the effects of four message frames on participants' attitudes toward the COVID-19 vaccine and their vaccine intention. The primary purposes of this paper are to examine the 1) impact of loss vs. gain frames and individual vs. collective frames and 2) role of perceived benefits on participants' attitudes toward the COVID-19 vaccine and their vaccine intention. Our findings show that participants with higher perceived benefits and exposed to the loss frame showed higher positive attitudes toward the COVID-19 vaccine and greater intention to vaccinate. Similar patterns were revealed in case of the individual frame message. Implications are discussed.